Curcumin Improved Intestinal Epithelial Barrier Integrity by Up-Regulating ZO-1/Occludin/Claudin-1 in Septic Rats. (7th June 2022) - Liu, Xiaofeng; Zhu, Hongquan
Abstract : Objective . To investigate the protective effect and mechanism of curcumin on intestinal barrier function in rats with enterogenic sepsis. Methods . Rats were divided into Sham group (Sham), Model group (Model), low-dose curcumin group (100 mg/kg), and high-dose curcumin group (200 mg/kg), with 10 rats in each group. Sepsis model was established in model group, low-dose curcumin group, and high-dose curcumin group. After drug intervention, hematoxylin-eosin (HE) staining was used to observe the histopathological changes of small intestine in each group. The levels of TNF- α, IL-1 β, and IL-6 in serum and intestinal tissues of rats were determined by ELISA. The expression of ZO-1, occludin, and claudin-1 in ileum was detected by QRT-PCR and Western blot. Western blotting was used to detect the expression of ERK/JNK signaling pathway, NF- κ B p65, apoptosis-related proteins Caspase-3, and TNF- α in rat intestinal tissues. Results . HE staining showed that curcumin treatment reduced epithelial cell shedding, interstitial edema, and apoptosis. Compared with model group, DAO activity, serum intestinal fatty acid binding protein (I-FABP), TNF- α, IL-6, and IL-1 β expression in curcumin group were decreased in a dose-dependent manner. Curcumin can upregulate the mRNA and protein expression levels of ZO-1, occludin, and claudin-1 in ileum of CLP-induced rats. In addition, curcumin inhibits NF- κ B p65 activation and apoptosis by regulating ERK/JNK signaling pathway. Conclusion . Curcumin can reduce inflammatory response and upregulate the expression of intestinal tight junction proteins ZO-1, occludin, and claudin-1 in rats with enterogenic sepsis, and protect intestinal barrier function.